Manipulating and Imaging the Shape of an Electronic Wave Function by Magnetotunneling Spectroscopy (2010)
We measure the current due to electrons tunneling through the ground state of hydrogenic Si donors placed in a GaAs quantum well in the presence of a magnetic field tilted at an angle to the plane of the well. The component of B parallel to the direction of current compresses the donor wave function. By measuring the current as a function of the perpendicular component of B, we probe how the magnetocompression affects the spatial form of the wave function and observe directly the transition from Coulombic to magnetic confinement at high fields. Manipulating and Imaging the Shape of an Electronic Wave Function by Magnetotunneling Spectroscopy | Request PDF. Available from: https://www.researchgate.net/publication/49752054_Manipulating_and_Imaging_the_Shape_of_an_Electronic_Wave_Function_by_Magnetotunneling_Spectroscopy [accessed Aug 06 2018].